Efficacy of etanercept for treatment of Crohn's related spondyloarthritis but not colitis. Issue 1 (1st January 2003) - Marzo-Ortega, H; McGonagle, D; O'Connor, P; Emery, P
Abstract : The seronegative spondyloarthropathies (SpAs) are associated both with clinical and subclinical colitis. Recently biological blockade with the tumour necrosis factor alpha (TNFα) antagonists infliximab and etanercept has been shown to be effective in the treatment of SpA. However, only infliximab is efficacious in the treatment of colitis in patients with Crohn's SpA. We report on two patients with SpA and associated Crohn's disease treated with etanercept whose arthritis showed an excellent response with complete resolution of spinal pathology, whereas their Crohn's disease persisted or flared. These findings suggest that the effect of TNFα blockade in SpA differs between the joint and the bowel.